We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
397
2
avatar

Which expression is equivalent to four?

A.

(10 – 4) + 2

B.

10 – 4 + 2

C.

10 – (4 + 2)

D.

(10 – 4 + 2)

 Jun 13, 2018
 #1
avatar
0

C -  10 - (4 + 2)  do the brackets first.

10 - (6) = 4

 Jun 13, 2018
 #2
avatar
0

A.

(10 – 4) + 2

= 6 +2 

= 8

B.

10 – 4 + 2

= 10 + 2 - 4

= 12-4

= 8

C.

10 – (4 + 2)

= 10 - 6

= 4

D.

(10 – 4 + 2)

=> same as B

So, C is the correct answer

 Jun 13, 2018

4 Online Users